2018
DOI: 10.1111/asap.12147
|View full text |Cite
|
Sign up to set email alerts
|

Ageism and Sexism in the 2016 United States Presidential Election

Abstract: The 2016 U.S. Presidential Election provided a unique opportunity to examine how ageism and sexism may impact attitudes (perceived presidential qualities and endorsement of positive and negative age stereotypes) toward Hillary Clinton and Donald Trump. Community participants (N = 875) indicated their attitudes and voting intentions 3 weeks before the election. Endorsement of positive and negative age stereotypes and perceived presidential qualities for Clinton and Trump varied based on participants' attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 54 publications
5
37
0
Order By: Relevance
“…However, considering that Biden and Sanders are almost 10 years older than Warren, and Biden's age did not prevent him from securing both the Democratic nomination and the eventual Presidency, this suggests that age‐related stereotypes did not impede him. This mirrors the situation for Trump in the 2016 campaign (Lytle et al., 2018).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, considering that Biden and Sanders are almost 10 years older than Warren, and Biden's age did not prevent him from securing both the Democratic nomination and the eventual Presidency, this suggests that age‐related stereotypes did not impede him. This mirrors the situation for Trump in the 2016 campaign (Lytle et al., 2018).…”
Section: Discussionsupporting
confidence: 71%
“…Age has been a concern for the past few election cycles and, even though it was not a central focus of the original study (Zurbriggen & Sherman, 2010), concerns were raised then around McCain's age, that at 71, he would have become the oldest newly elected president (Horsley, 2008). In 2016, both Trump and Clinton had age stereotypes applied to them (though only Clinton had her age used against her, despite being younger than Trump; Lytle et al., 2018). In a way, the results from our study differ from the past treatment of age, because we found that age stereotypes were primarily focused on Biden, despite all three front‐runners being over 70 (Padilla et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…compared to older men (Chrisler et al, 2016). Similarly, qualified older women are perceived differently when seeking leadership positions as they face both sexism and ageism as impediments to securing positions of power (Lytle et al, 2018).…”
Section: Age and Gendermentioning
confidence: 99%
“…Census Bureau, 2011). Despite this substantial increase in older lesbian, gay, and bisexual (LGB) adults and the disproportionate number of older women, little research is directed toward understanding the unique aging experiences of older sexual minorities (Fredriksen-Goldsen & Muraco, 2010) nor older women (Chrisler et al, 2016; Lytle, Macdonald, Dyar, & Levy, 2018). In light of research highlighting the need and value of studying intersectionality (Fredriksen-Goldsen & Muraco, 2010; Lytle et al, 2018) and lack of research examining sexual orientation or gender differences among older adults, the present investigation attempts to address these gaps in the literature.…”
mentioning
confidence: 99%